Oral health and oral health needs among patients with serious mental illness: reflections and experiences of psychiatric staff in Sweden - Charlotte Johansson; Linda Beckman; Ingrid Rystedt; Ann-Catrin André Kramer; Ulrika Lindmark (BMC Psychology)
Abstract Background Due to organizational structures, there is a gap between psychiatric and dental care services that limits collaboration and knowledge sharing, and this can have a negative impact on patients’ oral health or general health and vice versa. To facilitate the integration between dentistry and psychiatry, more insight and knowledge is needed on psychiatric staffs’ work with patients’ oral health. Therefore, the aim of this study was to explore the experiences of psychiatric staff regarding patients’ oral health and meeting their oral health needs. Methods Using a semi-structured guide, staff (n = 13) in Swedish psychiatric and forensic settings and in municipal housing support services were interviewed about their experiences with patient oral health. The interviews took place between April 2022 and June 2023. The data were analysed with inductive qualitative content analysis. Results This study identified challenges such as organizational issues, complex administrations, and a lack of tools for integrating oral health into psychiatric care. The patients perceived to face daily health-related challenges, and the informants identified opportunities to include oral health into tools for health promotion and the facilitation of healthy lifestyle changes. Conclusion Psychiatric staff possess central knowledge and insight into the life situations of patients with severe mental illness, and psychiatric staff consider dental staff to be key partners. Collaboration between psychiatric and dental staff is essential for developing strategies to integrate oral health perspectives into current screening and psychopedagogical models and practices.